Recurrent Catamenial Pneumothorax Suggestive of Pleural Endometriosis - Shawky Z. A. Badawy; Pujan Shrestha (Case Reports in Obstetrics and Gynecology)
A 42-year-old multiparous patient presented for consultation as a referral for management of recurrent catamenial pneumothorax. Evaluation by a pulmonologist failed to reveal any chest masses. She was treated for endometriosis using Danazol 800 mg daily for 6 months. Pneumothorax did not recur during treatment and during follow-up visits.